Hvor mye ren kjernekapital må bankene sette av ved utlån til næringseiendom?; How much CET1 capital must banks set aside for commercial real estate exposures? - Henrik Andersen (Norges Bank, 2019)
– The Ministry of Finance has proposed a temporary capital requirement (risk weight floor) for commercial real estate (CRE) exposures in Norway, applicable to the largest banks. CRE is the sector where banks have historically incurred the largest losses during crises. Since CRE loan losses are low in normal times, capital requirements for CRE loans should be based on losses incurred during crises. My calculations suggest that the level of capital required with the proposed risk weight floor is high enough to cover banks' CRE loan losses[1] during the downturn in 2002-03, but lower than the CRE loan losses incurred during the banking crisis of 1988-93. This also applies if I assume that the profit generated by CRE loans cover some of the losses. On the other hand, risk weight floors should not be set to a level that weakens banks' incentives to provide low-risk loans, implying that such minimum requirements should not be set too high. This will be of particular importance for lending segments where credit risk varies widely, such as the CRE market. All in all, this suggests that the proposed minimum requirement is at a reasonable level.
hdl:11250/2653108
Keywords: 330; Banks; capital requirements; loan losses; commercial real estate; credit risk